Small Animal Imaging : Basics and Practical Guide - Kiessling, Fabian; Pichler, Bernd J.; Hauff, Peter (Springer International Publishing : Imprint: Springer, 2017)
This textbook is a practical guide to the use of small animal imaging in preclinical research that will assist in the choice of imaging modality and contrast agent and in study design, experimental setup, and data evaluation. All established imaging modalities are discussed in detail, with the assistance of numerous informative illustrations. While the focus of the new edition remains on practical basics, it has been updated to encompass a variety of emerging imaging modalities, methods, and applications. Additional useful hints are also supplied on the installation of a small animal unit, study planning, animal handling, and cost-effective performance of small animal imaging. Cross-calibration methods and data postprocessing are considered in depth. This new edition of Small Animal Imaging will be an invaluable aid for researchers, students, and technicians involved in research into and applications of small animal imaging.
Keywords: Medicine.; Laboratory medicine.; Pharmacology.; Radiology.; elektronické knihy; electronic books